KERAGAAN USAHATANI PADI DAN KONTRIBUSI NYA TERHADAP PENDAPATAN RUMAHTANGGA PETANI DI DESA MUKTIJAYA KEC. MUARA TELANG KABUPATEN BANYUASIN (JASEP, 2021)
Banyuasin Regency is one of the rice-producing regions in South Sumatra Province, ranked as the 4th largest nationally as a grain-producing district. with a geographical location at a position between 1.30° - 4.0° South Latitude and 104° 00' - 105° 35' East Longitude which stretches from the central part of South Sumatra Province to the eastern part with a total area of 11,832.99 Km2 or 1,183,299 Ha. The purpose of this paper is to analyze rice farming and its contribution to family income. This research was conducted in MUktijaya Village, Muara Telang District, Banyuasin Regency. The data collected consists of primary and secondary data. The results showed that the average income of rice farmers in Muktijaya Village, Muara Telang District was Rp. 20,132,837, with revenues of Rp. 24,932,000 per ha per year and production costs of Rp. 4,799,163. The average contribution of rice farming income to total household income is 32.88%, while the contribution of non-farming income is the largest contribution with a percentage of 45.32% and the smallest percentage of farming income other than rice is 21.80%. Keywords: Farming, rice, contribution